Patient Satisfaction on Covid-19 Handling in Primary Health Centers - Yustika Wirda Ningsih; Nasution, Azizah; Harahap, Urip (Talenta Publisher, 2022)
Primary health centers play important roles in preventing, detecting, and helping people to cope with the problems associated with the COVID-19 infection. Therefore, it is necessary to strengthen and optimize the role of primary health center, including pharmaceutical care. This prospective descriptive study aimed to evaluate the level of patient satisfaction on COVID-19 handling in seven primary health centers Medan, Sumatera Utara, Indonesia period January to April 2021. A self-designed questionnaire was distributed to a total of 617 patients admitted to the 7 primary health centers to assess the characteristics of the patients and the required data about patient satisfaction about nine-item pharmaceutical services provided, supporting facilities, and infrastructures. The patient satisfaction was assessed using a 4-point Likert scale categorized into very dissatisfied, dissatisfied, satisfied and very satisfied. The obtained data were analyzed using descriptive and Chi-Square analyses. Most (67%) of the respondents were females. The present study indicated that most respondents satisfied with the services provided.